The EU's role in income redistribution and insurance: Support, norm‐setter or provider? A review of justice‐based arguments. (23rd September 2021) - Vandenbroucke, Frank
Abstract: Income redistribution and insurance are core functions of welfare states. What role should the EU play in this domain? I examine the purchase of normative theorizing on social justice on this question, focusing on the contrast between three models of EU involvement: the EU as Support, which implies the sharing of resources through intergovernmental transfers; the EU as Provider, which implies EU cross‐border transfers towards individual citizens; the EU as Norm‐setter, which implies that the EU formulates normative policy ideals. I review different accounts of justice for the EU and how they bear on the choice between these models of EU involvement. Conceptions of "background justice" have some purchase in a debate on the EU's role, but that purchase is limited. They need to be complemented by shared conceptions of domestic justice and a degree of moral cosmopolitanism. I argue that a "European Social Union" should be a Support and Norm‐setter in the realm of insurance and redistribution. Through the establishment of interstate insurance, it would be a true "insurance union." It would engage in interstate redistribution, but there are no compelling reasons of justice for it to become a direct Provider of insurance or redistribution towards individual citizens.